EXAMINING THE ROLE OF OIP5 AND PCSK5 EXPRESSION IN PAPILLARY RENAL CELL CARCINOMA (pRCC) TUMORIGENESIS - Huong, Bryan (My University, 2022)
Renal cell carcinoma (RCC) is a cancer that originates from renal tubular epithelial cells in the kidneys. Studies focusing on RCC are vital as it accounts for around 3% of all human cancers as of 2014 and accounts for over 90% of cancers affecting the kidneys. Being a heterogenous disease, RCC consists of multiple subtypes including papillary RCC (pRCC) with a 10% incidence rate. The heterogenous nature of RCC makes it difficult to determine biomarkers and therapeutic treatments that can provide adequate treatment targeting RCC in different patients, which stresses the need to discover as many therapeutic targets as possible. OIP5, also known as Mis18β, is a 25-kDa protein that is accumulated in the telophase-G1 centromere during mitosis and plays a role in centromere/kinetochore structure formation and functionality. As Mis18β, it interacts with Mis18α in a heterotetramer complex to bind and localize centromeric protein A (CENP-A) to the proper centromere region to allow for formation for centromere/kinetochore formation and function. OIP5 is normally highly expressed in the testes but recent studies have suggested that OIP5 overexpression is linked to the progression of some types of human cancers, including promoting pRCC cell proliferation and tumorigenesis. Furthermore, past studies have shown that other genes may impact RCC progression through regulation of cell growth and substrate activation extending past just the cell cycle. PCSK5 is another target of interest of focus in this study. Known also as PC6, it is a proprotein convertase which acts on precursor proteins to turn them into their active forms through post-translational modification and plays a role in cell growth and bone remodeling. This study aims to investigate the role of OIP5 during RCC progression both in vitro and in vivo with a focus on pRCC as well as investigate the expression of PCSK5 in conjunction with OIP5 and pRCC. In vitro studies confirmed previous results that OIP5 promotes colony formation in ACHN pRCC cells. Using a bioluminescent reporter alongside ACHN OIP5 and ACHN empty vector (EV) cell lines, mice were injected through renal subcapsule transplantation. It was seen that, while OIP5 produced larger tumors over a wider area after 12 weeks, metastasis did not appear to occur as largely as hoped though this may be due to limitations of the model. Analysis of the ACHN xenografts showed increased expression of PCSK5 and PLK1 in the OIP5 tumors. For PLK1, this is likely due to the close nature of its function with OIP5 during mitosis while PCSK5 may be regulated by OIP5 through an unknown mechanism or through microRNA miR-101-5p. Despite this, mRNA levels of PCSK5 were insignificant between OIP5 and EV groups. pRCC patient data showing PCSK5 expression levels showed a minor correlation with OIP5 expression, as well as higher expression at later pRCC stages and leading to reduced survival probability. Overall, this thesis analyzes the relationship of OIP5 in RCC, specifically pRCC, and introduces PCSK5 as another intriguing target for further study in treating pRCC.
Keywords: OIP5; pRCC; PCSK5; Cancer; Tumorigenesis